The level of peripheral blood circulating CD34+ cells is higher in acute promyelocytic leukemia patients with adverse prognostic factors. Issue 9 (20th October 2016) - Zeng, Hui; Yin, Ling-Di; Li, Ping; Yuan, Yan-hui; Guan, Chao-Yang; Xie, Ting; Zhang, Qi-Guo
Abstract : Introduction : The increased flow cytometry enumeration of peripheral blood circulating CD34+ cells in patients with acute leukemia has been found in our previous work. In this study, we also demonstrated that acute promyelocytic leukemia (APL) patients not only had elevated CD34+ cell count, but also had some clinical features. Methods : Fifty APL patients and 19 healthy volunteers were included in the study. The enumeration of circulating CD34+ cells, cytogenetic subgroup, immunophenotype analysis, and leukemic-related gene mutation detection were performed. Results : Some APL patients with higher count of CD34+ cells (≤10 × 10 6 /l) usually possessed one or more poor prognostic factors (higher WBCs count, PML/RARa gene complex fusion, chemotherapy-related APL, normal karyotype/complex karyotype abnormalities, CD56/CD34 antigen positive expression, FLT3-ITD positive mutation, myelofibrosis, and marrow necrosis). A cut-off value of 10 × 10 6 /l CD34+ cells may have the power to distinguish APL patients with above adverse clinical prognostic factor from other APL subjects. Conclusion : The circulating CD34+ cell count appears to increase in some APL patients and a higher CD34+ cell count may be indicative of inferior survival and serve as an adverse biomarker for APL.